Immunohistochemical Study: theoretical background and practical implementation - Nevmerzhytska, Nataliia; Rytikova, Nataliia (The Ukrainian Scientific Medical Youth Journal, 2025)
Immunohistochemistry (IHC) is a modern and highly effective method of tissue analysis that combines morphological examination with the ability to detect specific protein molecules expressed in cells. This technique is based on the use of antibodies that specifically bind to corresponding antigens—proteins, carbohydrates, or other biomolecules—present in cells or tissues. The main objective of IHC is not only to detect the presence of a specific protein but also to assess its localization (cytoplasmic, nuclear, or membranous), the intensity of expression, and its distribution within tissues. Immunohistochemistry is widely used in tumor diagnostics, where it enables precise identification of the histogenesis of neoplasms, determination of their clinico-biological subtypes, and evaluation of prognostic and predictive markers. Due to its broad range of applications, IHC is an indispensable tool not only in clinical pathology but also in scientific research. It allows researchers to study disease development mechanisms, particularly oncogenesis, disease progression, response to treatment, and to identify new therapeutic targets. The IHC protocol involves several key steps: fixation and preparation of the tissue sample, antigen retrieval, incubation with the primary antibody, application of a secondary antibody conjugated with an enzyme (typically peroxidase or phosphatase), visualization using chromogens (e.g., DAB—diaminobenzidine), and counterstaining (usually with hematoxylin). To enhance specificity and sensitivity, various signal amplification systems are employed, such as polymer-based systems or biotin-avidin complex methods. The quality of IHC results strongly depends on the correct selection of antibodies, proper reaction conditions, and quality control. Control procedures include the use of positive and negative samples, as well as careful interpretation of results considering staining intensity, the proportion of positive cells, and signal localization. While IHC staining evaluation is often performed manually by a pathologist, modern laboratories increasingly rely on automated systems and digital pathology to standardize and improve the accuracy of analysis. Recent advances in the field of IHC include multiplex staining, which allows simultaneous detection of multiple protein targets within a single sample, and integration with spatial transcriptomics techniques. Thus, immunohistochemistry is a powerful method for morphological visualization and molecular identification of cells, enabling the integration of classical histological approaches with modern biomolecular technologies. Its importance in diagnostics, prognostication, therapeutic decision-making, and fundamental research ensures its indispensable role in contemporary medicine and biology.